2020
DOI: 10.14203/mri.v45i2.285
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response and growth performance of spiny lobster (Panulirus homarus) juvenile rearing in recirculating aquaculture system with various shelter type

Abstract: Spiny lobster nursery is done to produce more adaptive and uniform juvenile lobsters quality. Shelters used in spiny lobster nursery served to reduce physical contact among lobsters in the rearing tank. The purpose of this study was to analyze the effect of different shelter types on physiological response and growth of spiny lobster (Panulirus homarus) juvenile rearing in recirculating aquaculture systems. Lobsters with an average weight of 50.07 ± 2.89 g were reared for 60 days. They were fed once a day with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…It may be of benefit to incorporate natural substrate to mimic a wild environment. For P. homarus juveniles, there was a preference for triangular‐shaped shelter over PVC piping, square and tube‐shaped shelters 136 . Other studies have shown that shelters suspended in the water column at open‐water sea sites significantly increased survival rates in spiny lobsters 17,137,138 .…”
Section: Health and Welfare Management Of Palinurus Elephasmentioning
confidence: 95%
See 1 more Smart Citation
“…It may be of benefit to incorporate natural substrate to mimic a wild environment. For P. homarus juveniles, there was a preference for triangular‐shaped shelter over PVC piping, square and tube‐shaped shelters 136 . Other studies have shown that shelters suspended in the water column at open‐water sea sites significantly increased survival rates in spiny lobsters 17,137,138 .…”
Section: Health and Welfare Management Of Palinurus Elephasmentioning
confidence: 95%
“…For P. homarus juveniles, there was a preference for triangularshaped shelter over PVC piping, square and tube-shaped shelters. 136 Other studies have shown that shelters suspended in the water column at open-water sea sites significantly increased survival rates in spiny lobsters. 17,137,138 Adding shell and sand into the rearing systems of European claw lobster (H. gammarus) has been shown to aid their claw development during stages 5-7.…”
Section: Stocking Density and Rearing Conditionsmentioning
confidence: 95%
“…Mortality risk during transportation can be reduced using a wet packing with oxygen in addition to preserving the physiological and metabolism activities that remain in optimum condition for puerulus (Arumugam et al 2020). The habitat difference in the rearing tank and transportation box due to shelter absence can trigger puerulus stress (Supriyono et al, 2017;Adiyana et al, 2020;Slamet et al, 2021). Administration of an anesthetic substance can also be used to reduce the stress level in transporting the living lobsters (Pozhoth and Jeffs, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Lobster culture was firstly conducted in a floating-net cage that produced financial profit to the culturists (Solanki et al, 2012;Daniels et al, 2015;Rao et al, 2020, Dinesh et al, 2022. This commodity has also been maintained indoor in the land, namely in the plastic tank with recirculation system (Adiyana et al, 2020). The lobster culture effort in a sub-mersive cage is being applied currently to provide more appropriate environment for this species physiologically (Fitzgibbon et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Vietnam is the world's main cultured lobster, although has currently been suffering from high mortality level, disease outbreak, and Chinese market dependence . Several studies have been performed to increase the lobster culture productivity, such as artificial feed improvement (Slamet et al, 2020), culture system (Mustafa, 2013), and maintenance technology (Adiyana et al, 2014;Adiyana et al, 2015;Adiyana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%